Collecting Narrative Data on Amazon's Mechanical Turk. Issue 4 (4th June 2015) - Grysman, Azriel
Summary Memory researchers collect data using Amazon's Mechanical Turk (AMT). Despite numerous reports documenting the reliability of data collected on this web site, no study of its uses for narrative memory research has been published. Participants reported narratives of stressful events and were recruited via AMT and in various formats with college students, including completing Internet surveys, typing in the presence of an experimenter, and verbal reports to the experimenter. Data were compared on linguistic indicators, event type reported, and questionnaire responses about these event narratives. AMT participants reported shorter event narratives than all groups of college students but reported stressful events that they self‐reported as more difficult than college students reporting via the Internet and used proportionally more negative emotion terms than college students reporting verbally to an experimenter. Factors such as context and demographics are considered, and recommendations are made for researchers using this web site. Copyright © 2015 John Wiley & Sons, Ltd.